Intersectionnalité, migrations et travail domestique : lectures croisées en France et aux États-Unis - Sophie Blanchard (EchoGéo)
This paper confronts two studies of women working in domestic service: an essay by Evelyn Nakano Glenn about the racialized construction of domestic work in the United Stades during the XXth century and an ethnographic study of domestic helpers in XXIth century France by Christelle Avril. These studies illustrate how intersectionnality can be a valuable tool to analyze the condition of racialized domestic workers.